Peculiarities of toxicodynamics and evaluation of hazard of the new avermectin class insecticides–abamectin and emamectin - Shpak B.I.; Antonenko A.M.; Korshun M.M. (Medičnì Perspektivi)
Based on the expert-analytical study of literature and websites on the results of toxicological experiments of varying duration, a hygienic evaluation of the new class of insecticides – macrocyclic lactones: abamectin and emamectin was done. It was found that by the parameters of acute oral and inhalation toxicity abamectin isreferred to a highly dangerous pesticides (class 1), by acute percutaneous toxicity – to moderately dangerous (3), by irritating and allergenic action – to low dangerous (4). According to LD50 emamectin in single administration into the stomach and on the skin belongs to class 3, by acute inhalation toxicity and irritation of the mucous membranes – to class 2 (dangerous), by skin irritation – to 3-4 class, having allergenic potential – 4 class of danger. CF-1 mice are animals most sensitive to the effects of avermectins due to polymorphism of their mdr 1a gene, coding P-glycoprotein. The main target organ to avermectin action was recognized to be the central nervous system. ADI of abamectin for humans was established at the level of 0,0002 mg/kg (the lowest NOAEL by systemic toxicity for parent and offspring generation was set in the experiment studying reproductive toxicity on rats – 0,12 mg/kg, a safety factor – 600) and emamectin – 0,001 mg/kg (the lowest NOEL was established in 16-day experiment on CF-1 mice – 0,1 mg/kg and a safety factor – 100).